Wireless Infidelity I: War Driving. - Berghel, Hal (Communications of the ACM, 2004)
It is informed that wireless technologies may be categorized in a variety of ways depending on their function, frequencies, bandwidth, communication protocols involved, and level of sophistication. They are broadly classified into the following categories: Wireless Data Networks (WDN), Personal Area Networks, Wireless Local Area Networks, of which the newer Wireless Metropolitan Area Networks and Wireless Wide Area Networks are offshoots, and satellite networks. WDN is a cluster of technologies primarily related to, developed for, and marketed by vendors in the telephony and handheld market. WDN includes protocols such as the Cellular Digital Packet Data, an older 19.2Kbps wireless technology that is still in use in some police departments for network communication with patrol cars; General Packet Radio Service and Code Division Multiple Access 2000, which are multiuser, combined voice and data 2.5- generation technologies that exceed 100Kbps; and Wireless Application Protocol, which provides wireless support of the Transmission Control Protocol/Internet Protocol suite and now provides native support of Hypertext Transfer Protocol and Hypertext Markup Language. INSET: URL PEARLS.